Relevance of Media to Language Learners and Students in Language Classrooms - Sabiya Nuridinova Alahiddinovna (Researchparks Publishing, 2023)
This article is aimed to enligten the effective use of media in education system as well as, to consider the stages of working with an foriegn language media in educational institutions and language lessons to give information about the application of an foreign language media to lessons in other languages as a way of developing educational and cognitive student interest.